Assessing African Vultures as Biomonitors and Umbrella Species - Thompson, Lindy J.; Krüger, Sonja C.; Coverdale, Brent M.; Shaffer, L. Jen; Ottinger, Mary Ann; Davies, John P.; Daboné, Clément; Kibuule, Micheal; Cherkaoui, S. Imad; Garbett, Rebecca A.; Phipps, W. Louis; Buechley, Evan R.; et al. (Frontiers in Conservation Science, 2021)
African vulture populations are in rapid decline, yet funding and other resources available for their conservation are limited. It is critical to prioritize research in applied conservation, which contributes to effective conservation strategies. Improving our understanding of African vultures as useful biomonitors could help alert conservation authorities to changes in ecosystem health. We used a systematic approach based on criteria selected a priori to objectively evaluate the potential of each of the 10 resident African vulture species as (i) a biomonitor species for ecosystem change, and (ii) an umbrella species for all of the African vulture species. Our results showed that, overall, certain aspects of vulture ecology (large population sizes, large body sizes, long lifespans, ease of detection, and their ability to be monitored over numerous seasons) support their suitability as biomonitors, while other ecological traits, including diet and public perceptions, could diminish suitability. The White-backed Vulture (Gyps africanus) was the best fit of the 10 vulture species in our assessment as both an avian biomonitor and an umbrella species for all the African vulture species. Meanwhile, significant knowledge gaps for other species inhibit their utility as biomonitors. For example, the Palm-nut Vulture (Gypohierax angolensis) scored poorly as an umbrella species, partly because relatively little is known about its natural history and ecology. While the White-backed Vulture may be useful as both an avian biomonitor and an umbrella species for all the African vulture species, it is important to conserve the entire suite of African vultures and thus retain the ecosystem services (cleaning, nutrient cycling, and cultural) to which they contribute. We suggest that using the White-backed Vulture as a biomonitor or umbrella species would be valuable as a conservation tool, to augment other methods for conserving African vultures. Lastly, we highlight how vultures could be used to identify ecosystems in crisis, where a rapid decline in numbers of vultures could be indicative of massive, imminent ecological, economic, and environmental impacts.